Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1098-1136(199904)26:2<176::aid-glia8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Edg-2 in myelin-forming cells: Isoforms, genomic mapping, and exclusion in Charcot-Marie-Tooth disease

Abstract: Edg‐2 is an heptahelical receptor whose spatio‐temporal distribution during rat brain development is consistent with a role in the control of myelination. We have now identified two splice variants of Edg‐2 mRNA in rat brain that encode two receptor isoforms differing by a stretch of 18 amino acids in the NH2‐terminal extracellular tail of the receptor. Prenatally (i.e., before oligodendrocyte myelination), the two variants detected by selective in situ hybridization are equally abundant, vary in parallel, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…In a similar manner, LPA has been shown to induce retraction of processes in immature, but not mature, CG4 oligodendroglial cell lines and OPCs (Dawson et al, 2003), an effect that is likely mediated by the Edg2/LPA1 receptor (Allard et al, 1998(Allard et al, , 1999. It is of note that in the same study, Dawson et al (2003) reported that in addition to LPA, S1P also induced process retraction of undifferentiated CG4 cells.…”
Section: Activation Of Edg8/s1p5 Induces Process Retraction In Pre-olmentioning
confidence: 70%
See 1 more Smart Citation
“…In a similar manner, LPA has been shown to induce retraction of processes in immature, but not mature, CG4 oligodendroglial cell lines and OPCs (Dawson et al, 2003), an effect that is likely mediated by the Edg2/LPA1 receptor (Allard et al, 1998(Allard et al, , 1999. It is of note that in the same study, Dawson et al (2003) reported that in addition to LPA, S1P also induced process retraction of undifferentiated CG4 cells.…”
Section: Activation Of Edg8/s1p5 Induces Process Retraction In Pre-olmentioning
confidence: 70%
“…The functional changes in the effect of Edg8/S1P5 activation may therefore relate to changes in receptor coupling with heterotrimeric G-proteins. This could occur by a variety of potential mechanisms including developmental switches of G-protein expression (i.e., from G12/13 to G␣ expression) or alternative splicing of the Edg8/S1P5 receptor resulting in changes to the coupling efficiency of the receptor to specific G-proteins, as suggested for Edg2/LPA1 (Allard et al, 1999). However, we were unable to isolate an alternative spliced variant of Edg8/S1P5 by comparison of RNA extracted from O4 ϩ -enriched pre-oligodendrocytes and mature oligodendrocytes (our unpublished data).…”
Section: S1p and Survival Of Mature Oligodendrocytesmentioning
confidence: 99%
“…Mice lacking the lpa 1 gene [lpa 1 (Ϫ/Ϫ) knockout mice] were expected to have nervous system defects, because lpa 1 is abundantly expressed in progenitor cells of the embryonic cerebral cortex and myelinating glial cells of both the peripheral and central nervous systems (1,2,24,38,39). Indeed, the most severe phenotype of lpa 1 (Ϫ/Ϫ) mice was approximately 50% neonatal lethality due to defective suckling, attributable to defective olfaction (14).…”
mentioning
confidence: 99%
“…The lpa 2 gene was the second such gene iden-tified, initially through sequence similarity searches using the lpa 1 sequence (3,11). Expression of the mouse lpa 2 transcript was found to be most abundant in kidney, testis, and embryonic brain, with low levels found in numerous other organs (13). When the LPA 2 receptor was expressed in mammalian cells, it mediated many of the same responses to LPA as LPA 1 (4,27), suggesting a functional redundancy in cells that express both receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation